(untitled) (Research, Society and Development, 2024)
Palliative care at the end of life is characterized by a differentiated approach, which highlights the care provided to people with terminal cancer. This study aims to describe palliative nursing care provided to children with terminal cancer. The methodology used was a narrative literature review, and searches were carried out in the PubMed, Scielo and LILACS databases, using the descriptors: palliative care nursing at the end of life, neoplasms seen in Decs/Mesh. The results included 12 publications. The discussion took place through the findings in the selected articles about palliative care at the end of life provided by the nursing team to children with cancer. The importance of the nurse’s role in palliative care at the end of life was inferred. It is concluded that the importance of the nurse’s role in palliative care at the end of life was highlighted, so that everyone participates in the care process: family and multidisciplinary team, but the nursing praxis in the scope of pediatric oncology, with an emphasis on the need Individualized and humanized nursing care is necessary at the bedside.